“Feminine invasion” women and Philippine pharmacy in the early twentieth century - Nery, Leo Angelo (2018)
Originally a male-exclusive profession in the nineteenth century, Philippine pharmacy became the domain of women in the early twentieth century. This sea change occurred as educational institutions began to cater to women’s career aspiration in pharmacy and especially after the US colonial school system introduced domestic science as a mandatory subject for girls, many of whom pursued pharmacy education in college. Women pharmacists set up retail drugstores in or near their residences, indicating pharmacy’s compatibility with women’s home-based roles. A contribution to gender history, this article shows that women actively challenged extant gender boundaries, which helped dismantle male exclusivity in other fields
Keywords: Pharmacists; Pharmacy; Public health; Feminism and education; Education of women; Women's studies; Feminism